(untitled) (ACME, 2023)
In 2011, the National Theatre in London celebrated the 30th anniversary of the stage production of Oresteia (Agamemnon, Choefori and Eumenides) with a major exhibition recounting the long process of creation of one of the most famous productions of English theatre of the last forty years; the adaptation and translation of Aeschylus’ Trilogy by the English poet and writer Tony Harrison, directed by Peter Hall (director of the National Theatre from 1973 to 1988) and the sets and masks of Jocelyn Herbert. This exhibition, curated by Cathy Courtney, came seven years after the major exhibition dedicated to the British stage designer entitled Jocelyn Herbert at the National (2004). This essay recounts the long creative path that led to the definition not only of an original translation, but also of a particular stage set that included the use of masks for male actors only, created by Herbert, one of Britain’s most famous stage designers. The preparatory materials have been made available online in recent years, thanks to a digitisation project of the National Theatre in collaboration with Google Culture Institute. It is precisely to Herbert’s masks and the various proposals and treatments of the Greek mask in a contemporary key that a final critical contribution is dedicated, which compares them with those of mask-maker and scholar of classical Greek theatre Ferdinando Falossi, as well as the digital video and photographic masks created respectively by Teatrino Giullare and Marzio Emilio Villa.